PERBEDAAN MODEL PEMBELAJARAN DISCOVERY LEARNING DAN PICTURE AND PICTURE TERHADAP KEMAMPUAN MENULIS CERITA PENDEK PADA SISWA KELAS IV SD - Janet Retno; Henny Dewi Koeswanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The background of this research is based on the results of observations in class IV SD Negeri Salatiga 03 showing that students' writing skills are very low this is due to the less than optimal learning model used by the teacher. Therefore, this study aims to determine the difference between discovery learning and picture and picture models on the ability to write short stories in grade IV elementary school students. The research was conducted at SD Negeri Salatiga 01 and SD Negeri Salatiga 03. The samples of this research were fourth grade students of SD Negeri Salatiga 01 with 27 students as the control class and fourth grade students of SD Negeri Salatiga 03 with 27 students as the experimental class. The type of research is Quasi Experimental Design. Data collection techniques using observation and tests. This research design is Nonequivalent Control Group Design. The data analysis technique was carried out by testing the experimental requirements. The results obtained show that the data is normally distributed and homogeneous. The results showed a significance value (2-tailed) of 0.026 <0.05. This means that H0 is rejected and Ha is accepted so that there is a significant difference in influence between the experimental class and the control class on the ability to write short stories in grade IV elementary school students. The difference in the average value of the posttest of the experimental class with the value obtained is 80.74 and the average value of the posttest of the control class with the value obtained is 83.19, then it shows that the ability to write short stories in students using the picture and picture learning method is better than the ability to write short stories in students using the discovery learning method.